High color rendering index white organic light-emitting diode using levofloxacin as blue emitter - 苗艳勤 高志翔 张爱琴 李源浩 王华 贾虎生 刘旭光 Tsuboi Taiju (Chinese physics B, 2015)
Levofloxacin （LOFX）, which is well-known as an antibiotic medicament, was shown to be useful as a 452-nm blue emitter for white organic light-emitting diodes （OLEDs）. In this paper, the fabricated white OLED contains a 452-nm blue emitting layer （thickness of 30 nm） with 1 wt% LOFX doped in CBP （4,4＇-bis（carbazol-9-yl）biphenyl） host and a 584-nm orange emitting layer （thickness of 10 nm） with 0.8 wt% DCJTB （4-（dicyanomethylene）-2-tert-butyl-6-（1,1,7,7- tetramethyljulolidin-4-yl-vinyl）-4H-pyran） doped in CBE which are separated by a 20-nm-thick buffer layer of TPBi （2,2＇,2＂-（benzene-1,3,5-triyl）-tri（1-phenyl-lH-benzimidazole）. A high color rendering index （CRI） of 84.5 and CIE chromaticity coordinates of （0.33, 0.32）, which is close to ideal white emission CIE （0.333, 0.333）, are obtained at a bias voltage of 14 V. Taking into account that LOFX is less expensive and the synthesis and purification technologies of LOFX are mature, these results indicate that blue fluorescence emitting LOFX is useful for applications to white OLEDs although the maximum current efficiency and luminance are not high. The present paper is expected to become a milestone to using medical drug materials for OLEDs.